PERBANDINGAN GUGUS FUNGSI DAN MORFOLOGI PERMUKAAN KARBON AKTIF DARI PELEPAH KELAPA SAWIT MENGGUNAKAN AKTIVATOR ASAM FOSFAT (H3PO4) DAN ASAM NITRAT (HNO3) - Vidyanova Anggun Mentari; Gewa Handika; Seri Maulina (Talenta Publisher (Universitas Sumatera Utara), 2018)
Indonesia is one of the biggest producent of palm oil in the world. According to Badan Pusat Statistik (Central Bureau of Statistics), on 2016 wide of the palm oil estate in Indonesia is 11.672.861 Ha. The waste of palm oil plantations so many and isn’t used optimal, for the example is oil palm frond. Oil palm frond is one of the wet of waste with the number of production as much as 19.143.492 ton on 2016. This research will discuss the comparison of functional group and surface morphology activated carbon of oil palm frond with use H3PO4 and HNO3 as an activator. This research purpose to know the comparison of functional group and surface morphology activated carbon of oil palm frond with use H3PO4 and HNO3 as an activator. The method includes impregnation, carbonization, and washing process. The concentration of activator is 20% with 400 oC activation temperature. This research is used morphology surface activated carbon analysis with SEM and FTIR spectrophotometer. The result of analysis with SEM show there is pore formed on activated carbon and the indentification with spechtrophotometer FTIR shows that activated carbon is contain of functional group are C=O, C=C, C-C, N=O, C-N, C-OH, CH2and C-H.